Estimating monthly temperature using point based interpolation techniques - Saaban, Azizan; Mah Hashim, Noridayu; Murat, Rusdi @ Indra Zuhdi (2013)
This paper discusses the use of point based interpolation to estimate the value of temperature at an unallocated meteorology stations in Peninsular Malaysia using data of year 2010 collected from the Malaysian Meteorology Department.Two point based interpolation methods which are Inverse Distance Weighted (IDW) and Radial Basis Function (RBF) are considered.The accuracy of the methods is evaluated using Root Mean Square Error (RMSE).The results show that RBF with thin plate spline model is suitable to be used as temperature estimator for the months of January and December, while RBF with multiquadric model is suitable to estimate the temperature for the rest of the months.